TL 18075 - Subtalar arthroscopic debridement for treatment of sinus tarsi syndrome: case series - Soares Baumfeld, Tiago; Barbachan Mansur, Nacime Salomão; Lemos, André; Xavier da Silveira, Juliana Doering; Furtado Fonseca, Lucas; de Souza Nery, Caio Augusto (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Sinus tarsi syndrome (SST) can be understood as a set of conditions that affect this anatomical region and manifest as common signs and symptoms. When the nonsurgical approach fails, subtalar arthroscopic debridement is a viable alternative with high rates of good outcomes. The objective of this study is to report the outcomes of subtalar arthroscopic debridement in 8 patients with SST refractory to conservative treatment. Methods: This is a retrospective study with 8 patients diagnosed with SST who underwent subtalar arthroscopic debridement of the sinus tarsi from January 2015 to January 2017, after 6 months of conservative treatment. All patients filled out an epidemiological questionnaire and underwent functional evaluation using the pain visual analog scale (VAS) and the American Orthopedic Foot and Ankle Society (AOFAS) scale preoperatively and at the final evaluation, after an average of 12 months (6-24 months). Results: All patients presented with intense synovitis in the region. Seven patients had remnants of talocalcaneal ligaments, and 6 had remnants of cervical ligaments. The AOFAS score increased by a mean of 30 points (from 51.75 preoperatively to 82.62 at the final evaluation), and the VAS decreased by a mean of 5 points (from 7.37 preoperatively to 2.12 at the final evaluation); these differences were significant, at p=0.043 and p=0.032, respectively. Six patients described the outcome as excellent, and 2 described it as good. No complications were reported. All patients resumed sports activities after 6 months of follow-up. Conclusion: Subtalar arthroscopic debridement is an effective and safe alternative in the treatment of SST refractory to conservative treatment. Further prospective studies are necessary to prove the outcome of this technique.